2008
DOI: 10.2353/ajpath.2008.080045
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40, a Marker of Simian Immunodeficiency Virus Encephalitis, Modulates the Biological Activity of Basic Fibroblast Growth Factor

Abstract: Human immunodeficiency virus encephalitis causes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 69 publications
6
102
1
Order By: Relevance
“…33 In contrast to MCP-1, YKL-40 appears to be more expressed in microglia than in neurons or astrocytes. 34 Increased YKL-40 expression is characteristic of many chronic inflammatory conditions, such as rheumatoid arthritis and irritable bowel syndrome, that are associated with destruction of the extracellular matrix and tissue remodelling. 35 It is therefore conceivable that YKL-40 causes remodelling of the extracellular matrix in the brain that could lead to neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…33 In contrast to MCP-1, YKL-40 appears to be more expressed in microglia than in neurons or astrocytes. 34 Increased YKL-40 expression is characteristic of many chronic inflammatory conditions, such as rheumatoid arthritis and irritable bowel syndrome, that are associated with destruction of the extracellular matrix and tissue remodelling. 35 It is therefore conceivable that YKL-40 causes remodelling of the extracellular matrix in the brain that could lead to neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…YKL-40 levels are also elevated in patients with a wide array of pathologies characterized by tissue destruction, ongoing inflammation, and development of fibrosis, such as rheumatoid arthritis, atherosclerosis, osteoarthritis, giant cell arthritis, and sarcoidosis (17), implicating its role in inflammatory processes and tissue remodeling. Increased levels of YKL-40 have also been reported in CNS pathologies, including Alzheimer disease, HIV-associated dementia, and multiple sclerosis (22)(23)(24). Although YKL-40 is produced by activated microglia (23), it has recently been shown that it is also secreted by reactive astrocytes (25).…”
mentioning
confidence: 99%
“…Increased levels of YKL-40 have also been reported in CNS pathologies, including Alzheimer disease, HIV-associated dementia, and multiple sclerosis (22)(23)(24). Although YKL-40 is produced by activated microglia (23), it has recently been shown that it is also secreted by reactive astrocytes (25).…”
mentioning
confidence: 99%
“…CHI3L1 modulates activity of basic fibroblast growth factor (bFGF) [49], binds to collagen types I, II, and III, and modulates the rate of collagen fibril formation [48]. No one of these interactions is shown for CHI3L2, and no protein-protein interaction partners were found up to now (particularly, there are no reports about participation of CHI3L2 in any proteinprotein interaction in BioGRID, HPID, MIPS, MINT, IntAct, DIP, and BRITE databases).…”
Section: Discussionmentioning
confidence: 99%